Nuclear Magnetic Resonance Imaging of Li-ion Battery - D. Ohno; Y. Iwai; J. Kawamura (Atom Indonesia, 2010)
Nuclear magnetic resonance (NMR) imaging has high sensitivity to proton (1H) and lithium (7Li). It is a useful measurement for electrolyte in Li-ion battery. 1H NMR images of lithium ion battery which is composed of LiMn2O4 / LiClO4 + propylene carbonate (PC) / Li-metal have been studied. 1H NMR images of electrolyte near cathode material (LiMn2O4) showed anomalous intensity distribution, which was quite inhomogeneous. From NMR images as a function of repetition time (TR), it was concluded that the anomalous intensity distribution was not due to change of relaxation time but an indirect (spatial) para-magnetization effect from cathode material. The paramagnetization induced by high magnetic field distorts linearity of magnetic gradient field, leading to apparent intensity variance. This functional image is an easy diagnostic measurement for magnetization of cathode material, which allows the possibility to check uniformity of cathode material and change of magnetization under electrochemical process. Received: 7 October 2010; Revised: 1 December 2010; Accepted: 17 December 2010